Neuropsychiatric Symptoms in Elderly With Dementia During COVID-19 Pandemic: Definition, Treatment, and Future Directions - Simonetti, Alessio; Pais, Cristina; Jones, Melissa; Cipriani, Maria Camilla; Janiri, Delfina; Monti, Laura; Landi, Francesco; Bernabei, Roberto; Liperoti, Rosa; Sani, Gabriele (Frontiers in Psychiatry, 2020)
Background Neuropsychiatric symptoms (NPS) of dementia, such as anxiety, depression, agitation, and apathy, are complex, stressful, and costly aspects of care, and are associated to poor health outcomes and caregiver burden. A steep worsening of such symptoms has been reported during Coronavirus Disease 2019 (COVID-19) pandemic. However, their causes, their impact on everyday life, and treatment strategies have not been systematically assessed. Therefore, the aim of this review is to provide a detailed description of behavioral and psychopathological alterations in subjects with dementia during COVID-19 pandemic and the associated management challenges. Methods A PubMed search was performed focusing on studies reporting alterations in behavior and mood and treatment strategies for elderly patients with dementia, in accordance with PRISMA guidelines. The following search strategy was utilized: (COVID* OR coronavirus OR “corona vir*” OR SARS-CoV-2) AND (dementia OR demented OR dement* OR alzheimer* OR “pick’s disease” OR “lewy body” OR “mild cognitive” OR mild cognitive impairment OR MCI). Results Apathy, anxiety and agitation are the most frequently NPS during the COVID-19 pandemic and are mainly triggered by protracted isolation. Most treatment strategies rely on pharmacotherapy; technology is increasingly utilized with mixed results. Conclusions NPS of dementia during COVID-19 appear to arise from social restrictions occurring as a consequence of the pandemic. Implementation of caregiver support and the presence of skilled nursing home staff are required to restore social interaction and adjust technological support to the patients’ needs.